2005
DOI: 10.1037/0735-7044.119.5.1195
|View full text |Cite
|
Sign up to set email alerts
|

Hyperphagia induced by GABAA receptor-mediated inhibition of the nucleus accumbens shell: Dependence on intact neural output from the central amygdaloid region.

Abstract: To investigate the role of corticolimbic input in modulating feeding-related nucleus accumbens (Acb) circuitry, researchers temporarily deactivated sites within the basolateral amygdaloid complex (BLA) or central amygdaloid region (CeA) via GABA(A) agonist (muscimol) infusions and measured feeding responses following muscimol infusions into the Acb shell. Hyperphagia elicited by intra-Acb shell muscimol was not altered by coinfusions of intra-BLA muscimol. In contrast, muscimol infusions into the CeA dose-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 79 publications
1
30
3
Order By: Relevance
“…Perhaps more germane to this discussion, shellmediated hyperphagia does not translate into enhanced operant responding for food (Zhang et al 2003). Moreover, hyperphagia-inducing shell manipulations during operant training enhance the acquisition of responding for food reward (Hanlon et al 2004;Baldo et al 2005). Thus, the feeding response elicited from the shell appears to resemble the release of fixed-action feeding patterns, in a manner reminiscent of stimulus-driven feeding elicited from the lateral hypothalamus Baldo and Kelley 2007).…”
Section: Mapping Behavior Onto the Circuits Of The Ventral Striatummentioning
confidence: 92%
“…Perhaps more germane to this discussion, shellmediated hyperphagia does not translate into enhanced operant responding for food (Zhang et al 2003). Moreover, hyperphagia-inducing shell manipulations during operant training enhance the acquisition of responding for food reward (Hanlon et al 2004;Baldo et al 2005). Thus, the feeding response elicited from the shell appears to resemble the release of fixed-action feeding patterns, in a manner reminiscent of stimulus-driven feeding elicited from the lateral hypothalamus Baldo and Kelley 2007).…”
Section: Mapping Behavior Onto the Circuits Of The Ventral Striatummentioning
confidence: 92%
“…This constitutes a PPI . We sought to identify "target" regions that showed differential connectivity according to the context (appetizing vs bland) with each of two source regions (the ventral striatum and the amygdala) consistently implicated in feeding and food reward by animal and human research (Rolls et al, 1980;Nishijo et al, 1988;Masuda et al, 1997;Baldo et al, 2005;Balleine and Killcross, 2006;O'Doherty et al, 2006); the amygdala and ventral striatum have also been implicated in other types of rewards such as money (Knutson and Bossaerts, 2007) and positive feedback (Cools et al, 2002). We also explored any connectivity pattern arising from the ventral ACC, given its wider role in emotion regulation (Davidson et al, 2000;Ochsner and Gross, 2005;Delgado et al, 2008) and extinction (Phelps et al, 2004;Delgado et al, 2008) (supplemental material, available at www.…”
Section: Methodsmentioning
confidence: 99%
“…Animal research has implicated a broad network mediating feeding behavior, including subcortical (ventral striatum, amygdala, hypothalamus), allocortical (hippocampus), and frontal cortical regions (motor, premotor, orbital and medial prefrontal cortices) (Masuda et al, 1997;Nishijo et al, 1997;Baldo et al, 2005;Kelley et al, 2005). Functional imaging research in humans has also highlighted the role of these regions in food processing (Small, 2002;Killgore et al, 2003;DelParigi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, microinjection of GABA A receptor antagonist significantly blocked this inhibitory effect. Moreover, Baldo et al (20) observed that GABA A agonist infusion into the central amygdala reduced feeding elicited either by stimulation of the nucleus accumbens shell or by food deprivation. Similarly, infusion of TTX into the central amygdala blocked hyperphagia induced by the nucleus accumbens shell stimulation.…”
Section: Central Amygdalamentioning
confidence: 99%